2020
DOI: 10.3390/brainsci10050284
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Vitamin D in the Elderly to Resist COVID-19 and to Slow Progression of Parkinson’s Disease

Abstract: While we are still learning more about COVID-19, caused by the novel SARS-CoV-2 virus, finding alternative and already available methods to reduce the risk and severity of the disease is paramount. One such option is vitamin D, in the form of vitamin D 3 (cholecalciferol) supplementation, due to its potential antiviral properties. It has become apparent that older individuals have a greater risk of developing severe COVID-19, and compared to younger adults, the elderly have lower levels of vitamin D due to a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 48 publications
1
109
0
9
Order By: Relevance
“…It is not considered possible to achieve toxic levels via the sun alone, and supplementation for prolonged periods brings 25(OH)D to toxic levels only if the dose is consistently extraordinarily high (40,000 IU/day for many months) (28,88,91,92). The average naturally acquired 25(OH)D among equatorial tribal groups is 46 ng/ml (93).…”
Section: Controversy Concerning Risk Of Overdosementioning
confidence: 99%
See 1 more Smart Citation
“…It is not considered possible to achieve toxic levels via the sun alone, and supplementation for prolonged periods brings 25(OH)D to toxic levels only if the dose is consistently extraordinarily high (40,000 IU/day for many months) (28,88,91,92). The average naturally acquired 25(OH)D among equatorial tribal groups is 46 ng/ml (93).…”
Section: Controversy Concerning Risk Of Overdosementioning
confidence: 99%
“…The Endocrine Society found toxicity symptoms only at levels above 150 ng/ml (93). Toxicity is related to high calcium levels; 25(OH)D levels higher than 150 ng/ml in conjunction with high calcium levels produce weakness, GI symptoms and accompanying weight loss, arrhythmias, confusion, and kidney damage (28,88,92). Historically, toxic levels of vitamin D (>150 ng/ml) have almost exclusively been the result of industrial errors (inaccurate doses in supplements or fortified foods), and the few cases of toxicity from extremely high doses being intentionally taken for prolonged periods of time (sometimes under the direction of a health care practitioner) were rarely severe (94,95).…”
Section: Controversy Concerning Risk Of Overdosementioning
confidence: 99%
“…Thus, maintaining a serum 25(OH)D levels above 50 nmol/L could be recommended in COVID-19 disease. Indeed, Casey et al [16] concluded that daily supplementation of vitamin D potentially offer additional protection against COVID-19 and Ebadi et al [17] noticed that a high-dose vitamin D intervention could have a potential bene t in decreasing risk of COVID-19 severity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown that elevated PTH levels are associated with increased cardiovascular risk in the general population [22,23]. Mitnick et al [24] have found that the liver is an important source of the circulating interleukin-6 generated in response to PTH while Casey et al [16] have indicated that the most severe cases in COVID involving a pro-in ammatory state can lead to harmful outcomes mediated by a deregulated immune response involving interleukin-6 and other in ammatory signaling molecules. Moreover, Cheng et al [25] have found an association between higher serum concentrations of PTH and several in ammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of treatment options leads to pressure to find other ways to combat an infection that disproportionately affects older adults, the immunocompromised, and those with pre-existing medical conditions. Recently, we suggested that vitamin D 3 was a feasible option [41]. Another possible option is exercise.…”
Section: A Potential Sinister Predicament Includes Parkinson's Diseasmentioning
confidence: 99%